2013
DOI: 10.3354/dao02594
|View full text |Cite
|
Sign up to set email alerts
|

Megalocytivirus infection in orbiculate batfish Platax orbicularis

Abstract: Megalocytiviruses cause systemic disease in both marine and freshwater fishes, negatively impacting ornamental and food fish aquaculture. In this report, we characterize a megalocytivirus infection in a captive marine ornamental fish, the orbiculate batfish Platax orbicularis. Histologic examination revealed cytomegalic cells characterized by strongly basophilic granular intracytoplasmic inclusions within various organs. Transmission electron microscopy revealed icosahedral virus particles within the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…The results of this study enable a reassessment of index cases for megalocytivirus infection and provide the first evidence of TRBIV-like megalocytiviruses in ornamental fish species, as all previous molecular phylogenetic studies of megalocytiviruses from ornamental fish showed affinities with ISKNV (Song et al 2008, Weber et al 2009, Kurita & Nakajima 2012, Sriwanayos et al 2013, Subramaniam et al 2014, Mohr et al 2015, Nolan et al 2015. To the extent that the samples analysed in this investigation are representative, the lack of detection of ISKNV megalocytiviruses in ornamental fish prior to the mid-1990s (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The results of this study enable a reassessment of index cases for megalocytivirus infection and provide the first evidence of TRBIV-like megalocytiviruses in ornamental fish species, as all previous molecular phylogenetic studies of megalocytiviruses from ornamental fish showed affinities with ISKNV (Song et al 2008, Weber et al 2009, Kurita & Nakajima 2012, Sriwanayos et al 2013, Subramaniam et al 2014, Mohr et al 2015, Nolan et al 2015. To the extent that the samples analysed in this investigation are representative, the lack of detection of ISKNV megalocytiviruses in ornamental fish prior to the mid-1990s (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, all megalocytivirus isolates derived from ornamental fish species that have been subjected to phylogenetic analyses of the major capsid protein (MCP) gene have been shown to be members of the infectious spleen and kidney necrosis (ISKNV) subgroup (Sudthongkong et al 2002b, Jeong et al 2008, Song et al 2008, Weber et al 2009, Kurita & Nakajima 2012, Sriwanayos et al 2013, Nolan et al 2015. A potential exception has been recorded in African lampeyes, in which the sequence of the adenosine triphosphatase (ATPase) gene of African lampeye iridovirus (ALIV) appears to cluster with red seabream-like megalocytivirus isolates even though phylogenetic analysis of the MCP gene sequence places this isolate firmly as a member of the ISKNV subgroup (Sudthongkong et al 2002b, Kurita & Nakajima 2012.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report of molecular diagnosis of Megalocytivirus in Brazil in red piranhas, which draws attention due to the problems that the virus can cause. The occurrence of the nonspecific clinical signs 3,4,6,12 in red piranhas after feeding with live fish, associated with the findings in the necropsy of organ hemorrhage, have led to the suspicion of diseases of viral etiology. Further studies are needed to confirm whether fish used as food were a source of Megalocytivirus infection for native species.…”
Section: Resultsmentioning
confidence: 99%
“…Some fish may have visible hemorrhagic fluid in the body cavity. 4,6 The aim of the study was identify red piranhas (Pygocentrus nattereri) used as ornamental fish suspected of viral infection by molecular diagnosis, and to alert to the presence of Megalocytivirus in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The Iridoviridae comprise 5 genera: Ranavirus infecting poikilothermic vertebrates (Chinchar 2002, Whittington et al 2010, Chinchar & Waltzek 2014, Peng et al 2015; Megalocytivirus (Kurita & Nakajima 2012) causing systemic infections in fish (Inouye et al 1992, Subramaniam et al 2012, Sriwanayos et al 2013; Lymphocystivirus usually causing superficial disease (skin, fins) of fish, particularly flatfish (Pleuronectiformes) (Chinchar et al 2009, Yan et al 2011; and Iridovirus and Chloriridovirus infecting insects. In general, iridovirids and asfarivirids undergo DNA replication in the nucleus, followed by a second round of cytoplasmic DNA replication in perinuclear, often lucent, viromatrix (Zupanovic et al 1998, Huang et al 2006, Chinchar & Waltzek 2014 or viral factories (Salas & Andrés 2013) in which scattered icosahedral virions form, that become cytoplasmic paracrystalline arrays of mature virions (Zupanovic et al 1998, Majji et al 2006.…”
Section: Introductionmentioning
confidence: 99%